Development of comprehensive sexual education applications to improve adolescent reproductive health - Supriyadi, Supriyadi; Sodikin, Sodikin; Rahman, Ainun Najib Febrya; Wijaya, Ermadi Satria (Universitas Muhammadiyah Purwokerto, 2024)
Background: Adolescence is a period of emotional, mental, and physical change. To improve health-seeking behavior, reduce risky sexual behaviors, and increase knowledge about sexual and reproductive health, adolescents need support and access to services. The increasing availability of mobile apps requires a thorough evaluation of the quality and classification of these mobile apps so that accurate and evidence-based information can reach their users. Because smartphones are a private (intimate) technology, they are a promising means of closing this gap. However, research focusing on sexual health promotion programs delivered through smartphones is still rare.Purposes: Developing and testing a smartphone and internet-based comprehensive sex education app.Methods: This study employed Research and Development consisting of 4 stages, namely Literature Study, Development Stage, Validity Expert, and Trial.Result: The SEMAR app has seven features, ranging from mental health education to human relationships. The convenience score is 70%. The results of the trial show that this application effectively improves health education. 50-83% agree to use it. The sex stigma variable has the most extensive r (r=0.955), which means it has a solid and positive relationship.Conclusion: This application benefits adolescents in improving health education and adolescent reproductive health.